2005
DOI: 10.1007/s11244-005-2528-y
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic oxidation of aqueous methyl and dimethylamines by activated carbon

Abstract: The catalytic wet air oxidation (CWAO) of methyl and dimethylamines was studied. A commercial peach stones activated carbon and its oxidized and reduced forms were used as catalysts. The observed catalytic behavior is related to the presence of oxygenated surface functional groups on the activated carbons. The N-compounds were selectively oxidized to nitrogen, water and carbon dioxide using these activated carbon catalysts. It is proposed that the quinonic surface groups are responsible for the selective catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…In order to enhance the quantity of oxygenated surface functional groups, the original PC material was modified by a liquid phase oxidation treatment reported in other previous works [19]: the solid was kept in contact to a HNO 3 solution (6 mol/L) for 1 h at 80°C in a 250 mL round-bottom flask, using a ratio of 10 mL of acid solution/1.0 g of carbon. The recovered solids was washed with deionized water until neutrality and further dried in oven for 24 h at 110°C, resulting in O-PC material.…”
Section: Modification Of the Activated Carbonsmentioning
confidence: 99%
“…In order to enhance the quantity of oxygenated surface functional groups, the original PC material was modified by a liquid phase oxidation treatment reported in other previous works [19]: the solid was kept in contact to a HNO 3 solution (6 mol/L) for 1 h at 80°C in a 250 mL round-bottom flask, using a ratio of 10 mL of acid solution/1.0 g of carbon. The recovered solids was washed with deionized water until neutrality and further dried in oven for 24 h at 110°C, resulting in O-PC material.…”
Section: Modification Of the Activated Carbonsmentioning
confidence: 99%
“…The untreated samples were denoted as CGRAN and DARCO, while the Hetreated samples were denoted as CGRAN-He and DARCO-He. ) at 80 °C for 1 h following a procedure reported by Aguilar et al 12 . The samples were then thoroughly washed with water until a neutral pH of the filtrate was obtained, and then dried at 110ºC for 10 h. The samples were denoted as Darco-N3 and Darco-N6 according to the concentration of HNO 3 used (3 mol L -1 and 6 mol L -1 , respectively).…”
Section: Thermal Modification With Helium Treatmentmentioning
confidence: 99%
“…The overall efficiency of both carbon materials should reflect a combined effect of their mesoporous character and surface oxygen functionality (as measured by the CO/CO 2 ratio obtained by TPD). In CWAO of aqueous methyl and dimethylamines using activated carbons as catalysts, the observed catalytic activity was related to the presence of oxygenated functional groups on the activated carbons, being proposed that the quinone surface groups (releasing CO by TPD) were those responsible for the catalytic activities, while carboxylic, lactone and anhydride groups, releasing CO 2 , were responsible for a catalytic activity inhibition [19]. In a recent study [26] we discovered that the CX catalyst undergoes surface modification (decrease of the CO/CO 2 ratio) when used in the CWAO process, supporting our interpretation on the catalytic role of the groups releasing CO by TPD.…”
Section: Effect Of Catalyst Texture and Surface Chemistrymentioning
confidence: 99%
“…Interestingly, we have noticed that the aniline removal efficiency and the selectivity to non-organic compounds obtained with such supported Pt catalysts were dependent on the mesoporous character and on the concentration of surface oxygen functional groups of the corresponding support. Other research groups also reported on carbon materials as promising catalysts for the CWAO of aromatic compounds, such as phenol and aniline [14][15][16][17] and of nitrogen containing compounds, such as ammonia and amines [18,19]. The development of carbon materials and their application in CWAO, either as a catalyst support or directly as a catalyst, was recently reviewed [20].…”
Section: Introductionmentioning
confidence: 99%